An Integrated Information System Design for Managing National Hazardous Waste in Indonesia: A Proposal - Ashari Imamuddin (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2021)
Managing an information system of hazardous waste (HW), residual of business activities of hazardous materials, needs to be addressed as hazardous waste management (HWM) is one of crucial issues in global perspective. The waste directly and indirectly, can pollute or harm the environment, or endanger the environment, health, and survival of humans and other organisms. HWM is a set of activities which include reduction, storage, collection, transportation, utilization, processing and landfill. These activities involve waste generators, waste collectors, waste transporters, waste utilizer, waste processors, and waste landfill disposals. The paper aims to propose an integrated information system design of national HWM in Indonesia. The study was started by gathering requirements (by literature study, stakeholders interview, and focus group discussion with business people or workers related hazardous waste management), requirements analysis, established system requirements, and designed the information system based on the requirements. The study produced requirements of an integrated information system and system design which modelled using UML (unified modelling language). The design can be used as a foundation of detail design of processes, data, interface, and networks of a working prototype or working system.